Phenotypic stability of forty advanced lines of rice at Babahoyo, Ecuador - Maldonado , Cristina; Reyes , Walter; Duicela , Luis; Cobos , Fernando (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
The crosses between Oryza sativa L. and O. rufipogon Griff., create a high genetic diversity to develop rice varieties with high yield and phenotypic stability. In the present investigation, forty advanced lines of rice were evaluated in subsidiaries F5 (dry season) and F6 (rainy season), together with three commercial controls in the town of Babahoyo, Ecuador. A Randomized Complete Block Design (DBCA) was applied with three repetitions, recording morphoagronomic and productive characters. Statistical analyzes were applied and phenotypic stability was determined using the Eberhart and Russell, AMMI, Lin and Binns, PROMVAR models. The average morphoagronomic results were: days to flowering (72), vegetative cycle (98 days), plant height (111 cm), panicle sterility (6 %); the productive variables the results were: tillers per plant (32), panicles per plant (31), panicle length (27 cm), grains per panicle (168) and yield (8,100 kg.ha-1). The stable lines identified by the models: Eberhart and Russell were 1, 2, 10, 11, 13, 18, 25, 26, 30 and 37; AMMI identified lines 8 and 22; Lin and Binns to lines 2, 12, 18, 27, 37 and 40; and PROMOTE lines 2, 10, 13, 18, 25, 30, 38, 40 and 43; concluding that seven lines (2, 10, 13, 18, 25, 30 and 40) coincided with the applied models except AMMI. The average yield of the lines mentioned in the two seasons was 7,797 kg.ha-1, higher than the average of the commercial controls that obtained 6,809 kg.ha-1.